Wideband and high gain mmWave antenna with phase gradient metasurface - Soni, Devendra; Yadav, Dinesh; Tiwari, Manish (Institute of Advanced Engineering and Science, 2025)
This study presents a phase gradient metasurface (PGM) measuring 30 mm on each side and discusses its development. The use of multiple unit cell sizes is critical to the design of the PGM that was produced. A sand-timer-shaped monopole antenna was designed specifically for wideband millimetre wave (mmWave) applications. An antenna structure is reinforced with a PGM that was specifically designed to increase antenna gain over its bandwidth. This is done to increase the antenna gain overall. The antenna has a bandwidth of 9.18 GHz, which includes mmWave frequencies ranging from 20.78 GHz to 29.96 GHz. For a wideband response, the ground plane must contain flaws. These flaws must exist on the surface of the ground plane. This study presents an in-depth examination of the antenna, PGM design, and operating principles, backed up by experimental verification. The use of PGM results in a 5 dB increase in antenna gain, with an average improvement of 2 dBi across all frequencies.